1. Implementation of 4D proton therapy treatments with pencil beam scanning (PBS). (December 2018) - Fracchiolla, F.; Schwarz, M.; Dionisi, Francesco; Hild, Sebastian; Giacomelli, Irene; Lorentini, Stefano; Engwall, Erik; Esposito, Pier Giorgio; Amichetti, Maurizio
Abstract : Purpose: To report on the implementation, validation and results of the first two proton therapy PBS treatments of small amplitudes moving targets (thymoma) performed at our center. Methods: A real time optical tracking system was used to monitor the patient surface during the CT scan and treatment. It is able to trigger the beam during the treatment. Validation measurements on the machine were performed. A 4DCT (10 phases) and a free-breathing CT (FBCT) were used for the planning. The physician used the 4DCT for ITV delineation on the FBCT. The planning was performed on the FBCT. The approved plan was evaluated in two ways: - dose recalculation on each 4DCT phase - Interplay effect evaluation: every spot was assigned to a phase accordingly to the beam delivery and the breathing curve of the patient. The 10 doses were deformed and summed on the FBCT. The highest breathing amplitude recorded during 4DCT scan was used as gating threshold during treatment delivery. Results: The validation of the gating technique ensured a good quality of the beam delivery with interruptions. Dosimetric evaluation results of the plan and Duty Cycle information are shown in table for both patients: no interplay effect was highlighted. The second patient showed an overdosage to the coronary and Left Anterior Descending area but it was always below the constraints. Two breathing curves are shown in figure. The first patient breath is stable and within thresholds, whilst the second patient had more variations with multiple beam interruptions. Conclusions: We defined, validated and used for two patients a protocol for the treatment of small amplitude moving targets. The planning and delivery of the treatments gave very good results in terms of coverage, OARs sparing, 4D dose evaluation of the plan and interplay effect assessment.